Field potentials generated by group II muscle afferents in the lower-lumbar segments of the feline spinal cord - Riddell, J S (Blackwell Science Inc, 2000)
1. The actions of group II muscle afferents projecting to the lower-lumbar (L6 and L7) segments of the cat spinal cord were investigated by recording the cord dorsum and focal synaptic field potentials evoked by electrical stimulation of hindlimb muscle nerves. 2. Cord dorsum potentials recorded over the lower-lumbar segments were generally much smaller than those produced by group II afferents terminating within the midlumbar and sacral segments. Only group II afferents of tibialis posterior produced potentials with an amplitude (mean maximal amplitude 39 μV, n = 7) approaching that of potentials over other segments. 3. Focal synaptic potentials (mean maximal amplitudes 135–200 μV) were evoked by group II afferents of the following muscle nerves, listed in order of effectiveness: quadriceps, tibialis posterior (throughout L6 and L7), gastrocnemius soleus, flexor digitorum longus, posterior biceps-semitendinosus and popliteus (mainly within L7). 4. Field potentials were recorded in the dorsal horn (laminae IV–V) and also more ventrally in a region which included the lateral part of the intermediate zone (lateral to the large group I intermediate field potentials) and often extended into the ventral horn (laminae V–VII). The latencies of the group II potentials are considered compatible with the monosynaptic actions of the fastest conducting group II muscle afferents. 5. The results are compared with morphological evidence on the pattern of termination of group II muscle afferents in the lower-lumbar segments and with previous descriptions of the actions of group II muscle afferents in midlumbar and sacral segments.